2021
DOI: 10.1002/app.50669
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the cause for the unusual processing behavior of commercial partially bio‐based poly(butylene succinates) and their stabilization

Abstract: The commercially available partially bio‐based poly(butylene succinate) (PBS) and poly(butylene succinate‐co‐adipate) (PBSA) are subjected to prolonged and multiple extrusion cycles to investigate their thermal behavior. Empirically, both PBS and PBSA form branches at 190°C, with PBS possessing a higher tendency for branching than PBSA as studied by rheology and size exclusion chromatography (SEC). In each case, the branching is favored by fumaric acid moieties, making both PBS and PBSA susceptible to accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…Moreover, the study highlighted how at higher temperatures, branching occurred at the highest extent. Similar results were reported by (Hallstein et al, 2021) who clearly demonstrated branching phenomena in PBS and PBSA following extrusion cycles at 190°C. Such phenomena were associated to fumaric acid moieties detected both in PBS and PBSA, which disappear after extrusion processing thus suggesting reactions take place precisely in correspondence of fumaric acid moieties.…”
Section: Rheologysupporting
confidence: 90%
See 2 more Smart Citations
“…Moreover, the study highlighted how at higher temperatures, branching occurred at the highest extent. Similar results were reported by (Hallstein et al, 2021) who clearly demonstrated branching phenomena in PBS and PBSA following extrusion cycles at 190°C. Such phenomena were associated to fumaric acid moieties detected both in PBS and PBSA, which disappear after extrusion processing thus suggesting reactions take place precisely in correspondence of fumaric acid moieties.…”
Section: Rheologysupporting
confidence: 90%
“…Such high values are presumably ascribed to the afore mentioned hyper-branching phenomena which affect PBSA during melt-processing, always causing viscosity increase, no matter what working conditions are set (Hallstein et al, 2021).…”
Section: Rheologymentioning
confidence: 99%
See 1 more Smart Citation
“…The 1 H NMR spectra of the remaining structures were employed to detect the chemical compositions. As shown in Figure 7 , the characteristic nuclear magnetic resonance peak of the PBA at a chemical shift of 2.33 ppm still existed [ 33 ]. The mole ratios of the PBA/PBS in the THF-soaked blends were calculated based on the integrated areas of the two peaks at 2.33 ppm and 2.63 ppm, which increased with the initial feeding content of PBA, though much lower ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, an analysis of PBS end groups was done assigning the hydroxyl end group CH 2 –OH of PBS at 3.7 ppm; the heteronuclear long-range correlations of this end group were not associated with the new formed alkyl- and alkoxy-groups, thus confirming the proposed PBS-TMA reaction mechanism of Scheme 1 . 44 , 45 To evaluate changes on the PBS microstructure as a function of the number of SIS, a quantitative analysis through 1 H experiments was performed. Data are reported in Figure S11 .…”
Section: Resultsmentioning
confidence: 99%